Micro Structural Investigations and Mechanical Properties of Macro Porous Ceramic Materials from Capillary Suspensions. Issue 12 (22nd August 2014) - Dittmann, Jens; Willenbacher, Norbert
Abstract : Recently, we have introduced a novel, material‐independent processing method for producing macro porous ceramics with capillary suspensions as a stable precursor. A capillary suspension is a three‐phase system where a small amount of an immiscible secondary liquid is added to a suspension resulting in the formation of a sample spanning particle network. This technology provides open porosities well above 50% and pore sizes ranging from 0.5–100 μm. Here we focus on microstructure formation in the capillary suspensions and its impact on mechanical strength of the corresponding sintered parts. Based on the rheological data and SEM‐images, three regimes (I, II, III) are identified with distinctly different flow properties of the wet suspension and characteristic structural features of the sintered ceramic parts depending on the amount of added secondary liquid phase. The average pore size increases and the pore size distribution changes from monomodal (I) to bimodal (II) and broad multimodal (III) with increasing amount of secondary liquid phase. A clear correlation between the yield stress of the wet suspension and the porosity and pore size is observed for regime (I) and (II). Compressive and flexural strength as well as the Young's modulus monotonically decrease with increasing amount of the secondary liquid phase. Absolute values are mainly determined by the porosity and are well predicted by the Gibson & Ashby model for samples corresponding to regime (I) and (II). The broad pore size distribution in regime (III) results in a significantly lower mechanical strength.